A review of common beam hardening correction methods for industrial x-ray computed tomography - O.M.H. Ahmed; Song, Yushou (Penerbit Universiti Kebangsaan Malaysia, 2018)
X-ray computed tomography (XCT) became an important instrument for quality assurance in industry products as a non-destructive testing tool for inspection, evaluation, analysis and dimensional metrology. Thus, a high-quality image is required. Due to the polychromatic nature of X-ray energy in XCT, this leads to errors in attenuation coefficient which is generally known as beam hardening artifact. This leads to a distortion or blurring-like cupping and streak in the reconstruction images, where a significant decrease in imaging quality is observed. In this paper, recent research publications regarding common practical correction methods that were adopted to improve an imaging quality have been discussed. It was observed from the discussion and evaluation, that a problem behind beam hardening reduction for the multi-materials object, especially in the absence of prior information about X-ray spectrum and material characterizations would be a significant research contribution, if the correction could be achieved without the need to perform forward projections and multiple reconstructions.